Gender differences in the echocardiographic characteristics of the athletic heart - Pavlik, G.; Olexo, Z.; Banhegyi, A.; Sido, Z.; Frenkl, R. (Acta Physiologica Hungarica, 1999)
Differences between males and females in the effects of regular physical training on the heart were investigated by echocardiography in 579 male (nonathletes: 122, athletes: 457) and in 336 (nonathletes: 84, athletes: 252) female subjects of variable age. The age groups were: children (<15 yr.), adolescent-young (15-18 yr.), young adult (19-30 yr.), adult (31-45 yr.) and people elder than 45 yr older (45<). Hypertrophy characterised by relative left ventricular muscle mass (rel.LVMM) of the athletic heart was manifest also in the females, but in comparison with the males female values were much lower both in the unconditioned and in the conditioned groups. In people belonging to the oldest groups no differences were seen either between the males and females or between athletes and nonathletes. In comparing nonathletic subjects, females showed smaller left ventricular contractility as reflected by a higher LVET/QT ratio and an increased ability of diastolic relaxation as indicated by a higher E/A ratio. Physical training induced a more marked development when the initial level was lower, namely, in the contractility of the females, and in the compliance of the males. No intersex difference was seen in the modified regulation of the athletic heart, characterised by a lower resting heart rate and slower circumferential shortening velocity (VCF). Acta Physiol Hung 1999;86(3-4):273-8